Taibo, C. (2018). Anarquistas de ultramar: Anarquismo, indigenismo, descolonización. España: Libros de la Catarat, [207 páginas] - Marín Meneses, Benjamín (Anuario de la Escuela de Historia, 2022)
Reseña bibliográfica